2009
DOI: 10.1007/s10658-009-9511-6
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid biosynthesis and degradation play a role in early defence responses of bilberry (Vaccinium myrtillus) against biotic stress

Abstract: Bilberry (Vaccinium myrtillus) represents one of the richest flavonoid sources among plants. Flavonoids play variable, species-dependent roles in plant defences. In bilberry, flavonoid metabolism is activated in response to solar radiation but not against mechanical injury. In this paper, the defence reaction and biosynthesis of phenolic compounds of bilberry was studied after infection by a fungal endophyte (Paraphaeosphaeria sp.) and a pathogen (Botrytis cinerea). The defence response of bilberry was faster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
60
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 37 publications
10
60
1
2
Order By: Relevance
“…Studies also demonstrated that the biosynthesis of flavan-3-ols and PAs increased after infection by fungal endophytes in poplar (Pfabel et al, 2012) as well as after infection by pathogenic fungi in other plant species, such as bilberry (Vaccinium myrtillus; Koskimäki et al, 2009) and Fagus crenata (Yamaji and Ichihara, 2012). Increased accumulation of flavan-3-ols also has been recorded in Norway spruce (Picea abies) during infection by necrotrophic fungi (Danielsson et al, 2011;Hammerbacher et al, 2014).…”
Section: Discussionmentioning
confidence: 93%
“…Studies also demonstrated that the biosynthesis of flavan-3-ols and PAs increased after infection by fungal endophytes in poplar (Pfabel et al, 2012) as well as after infection by pathogenic fungi in other plant species, such as bilberry (Vaccinium myrtillus; Koskimäki et al, 2009) and Fagus crenata (Yamaji and Ichihara, 2012). Increased accumulation of flavan-3-ols also has been recorded in Norway spruce (Picea abies) during infection by necrotrophic fungi (Danielsson et al, 2011;Hammerbacher et al, 2014).…”
Section: Discussionmentioning
confidence: 93%
“…Many of the analysed flavanols in berry skins have already been reported as "responding" phenolic compounds to fungal and viral infections (Treutter and Feucht 1990;Gutha et al 2010). Moreover, Koskimäki et al (2009) hypothesized that the procyanidins might act as storage compounds in healthy tissue and become activated by degradation due to the infection. Salacha et al (2008) stressed the importance of the flavanols content in the context of wine browning; therefore, with BN infected grapes a susceptibility to browning can be expected.…”
Section: Phenolicsmentioning
confidence: 99%
“…Grapevine phytoalexins have been subject to numerous studies over the past decade, especially in the context of fungal infections, where the mechanisms of the inhibition of fungal enzymes in context of pathogenesis -the function of tannins and other phenolics -have been examined (Bavaresco et al 1997;Mikulič-Petkovšek et al 2009;Slatnar et al 2010;Landi and Romanazzi 2011). Figueiredo et al (2008) and Gutha et al (2010) reported different alterations in the biosynthetic pathways of flavonoids and the accumulation of individual phenol compounds due to fungal and viral infections, whilst Koskimäki et al (2009) suggested that the accumulation of individual phenolic compounds could be specific to each infection type. Moreover, Hren et al (2009) demonstrated a significant reprogramming of the transcriptome in leaf due to a BN infection, where nineteen genes from secondary metabolism (flavonoids, chalcones) were involved in up-regulated processes, and three genes in down-regulated processes.…”
Section: Introductionmentioning
confidence: 99%
“…KP218512), as well as regulatory gene VuTDR4 (GenBank Accession No. KP218511) were isolated according to the sequence homology with bilberry (V. myrtillus) (Jaakola et al 2002Koskimäki et al 2009;unpublished bilberry EST-database). The nucleotide sequences of VuMYBPA1, VuMYBC2 and VuMYBR3 were isolated with complete coding region and submitted to GenBank under accession numbers KR106180, KT186104 and KT186105, respectively.…”
Section: Cloning and Phylogenetic Analysismentioning
confidence: 99%